Consequences of quadratic frictional force on the one dimensional bouncing ball model - Leonel, Edson D. [UNESP]; Tavares, Danila F. [UNESP] (AIP Publishing, 2007)
Some dynamical properties of the one dimensional Fermi accelerator model, under the presence of frictional force are studied. The frictional force is assumed as being proportional to the square particle's velocity. The problem is described by use of a two dimensional non linear mapping, therefore obtained via the solution of differential equations. We confirm that the model experiences contraction of the phase space area and in special, we characterized the behavior of the particle approaching an attracting fixed point. © 2007 American Institute of Physics.
Keywords: Classical billiard; Fermi accelerator model; Nonlinear mapping